2010
DOI: 10.3109/07420528.2010.488958
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual Differences in Neurobehavioral Performance in Response to Increasing Homeostatic Sleep Pressure

Abstract: Neurobehavioral function deteriorates with increasing homeostatic sleep pressure during wakefulness. It has been claimed that some individuals exhibit a quicker rate of such deterioration than others, thus being more vulnerable than others to the detrimental impact of increasing homeostatic sleep pressure. Evidence supporting the claim, however, has been limited by methodological issues. To overcome these limitations, the current study used a 12-calendar-day, 28-h forced desynchrony (FD) protocol (sleep:wake p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…23 Results on tasks other than PVT are reported elsewhere. [24][25][26] Due to the wake extension in the sleep-restricted protocol (23.33 h sched-the sleep-restricted protocol (23.33 h scheduled wakefulness), there were 2 extra testing sessions in this protocol compared to the standard protocol (18.67 h scheduled wakefulness). All testing sessions were conducted individually in each participant's lounge room with participants seated in front of a blank wall in order to avoid distractions.…”
Section: Protocolsmentioning
confidence: 99%
“…23 Results on tasks other than PVT are reported elsewhere. [24][25][26] Due to the wake extension in the sleep-restricted protocol (23.33 h sched-the sleep-restricted protocol (23.33 h scheduled wakefulness), there were 2 extra testing sessions in this protocol compared to the standard protocol (18.67 h scheduled wakefulness). All testing sessions were conducted individually in each participant's lounge room with participants seated in front of a blank wall in order to avoid distractions.…”
Section: Protocolsmentioning
confidence: 99%
“…This is mathematically and statistically complicated and prone to misestimation of rhythm parameters [35]. The problem is compounded by the task-dependence of vulnerability to neurobehavioral impairment due to sleep loss [36,37], which may be mediated by use-dependent, pathwayspecific degradation of neuronal processing [38] and implies that there are task-specific differences in the impact of the homeostatic process [39]. These issues can be overcome by explicitly accounting for inter-individual variability during data analysis [7] but, to date, that approach has not been applied to the evaluation of putative task differences tied to circadian rhythmicity.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it has been suggested that the rate at which fatigue accumulates across the day varies as a function of prior sleep loss, consistent with the principles that: (1) acute and chronic sleep loss increase fatigue levels and that (2) high sleep loss increases the rate at which fatigue accumulates across the waking period (Matthews et al, 2012b). Some recently published laboratory studies have suggested that this increased fatigue accumulation rate is due to an interaction between circadian and homeostatic sleep/wake drives (Kosmadopoulos et al, 2017;Matthews et al, 2012aMatthews et al, , 2012bZhou et al, 2010). Moreover, these studies suggest that considering this interaction is necessary for the development of better fatigue-risk prediction models.…”
Section: Introductionmentioning
confidence: 78%